Adapting To Change: A Study Of Post-Pandemic Millennial Housing Preferences - Abdullah Bedi; Raden Aswin Rahadi (UNIVED Press, 2024)
The COVID-19 pandemic has fundamentally altered societal dynamics, particularly in the realm of residential preferences. This thesis investigates the shifting trends in post-pandemic housing preferences and their impact on residential decision-making. Key factors such as size, layout, amenities, location, outdoor spaces, and technological advancements are scrutinized to comprehend the shifting landscape of residential choices. The study reveals an increased emphasis on home office spaces and adaptable layouts as a response to the pandemic's transformative influence. It also highlights a growing inclination towards outdoor spaces like gardens and multi-function rooms due to the increasing trend of working at home during and after pandemic. Additionally, changing priorities in location selection and the rising importance of health-related aspects in home design are explored. Employing qualitative methods, the research conducts semi-structured interviews with eleven (11) diverse respondents to gain insights into post-COVID-19 house preferences and decision-making processes. The findings provide valuable guidance for real estate professionals, urban planners, and architects, aiding them in adjusting to the evolving needs and preferences of residents. Beyond academic realms, the study carries practical implications, contributing to the creation of innovative housing solutions aligned with changing preferences and responsive to post-pandemic societal demands. Ultimately, it seeks to inform policymakers and stakeholders, facilitating the development of sustainable residential environments that effectively address the evolving needs of individuals and communities in the aftermath of the COVID-19 pandemic.